Optimizing ventilation-perfusion lung scintigraphy: Parting with planar imaging - Reinartz, P.; Schirp, U.; Zimny, M.; Sabri, O.; Nowak, B.; Schäfer, W.; Cremerius, U.; Büll, U. (Nuklearmedizin - NuclearMedicine, 2001)
Aim of the study was to introduce and verify a ventilation-perfusion (V/Q) acquisition protocol that incorporates new developments in scintigraphy in order to allow for a more balanced comparison with other diagnostic procedures. Methods: In 103 patients suspect of having pulmonary embolism, V/Q scans were acquired exclusively with SPECT technique. Ventilation was done with ultrafine aerosol. Planar images in eight directions were reconstructed through addition of three consecutive SPECT projections. Three referees examined the scans in regard to type, localization, and extent of V/Q defects. Results: Using this protocol, significantly more defects, especially of subsegmental size, were detected (p <0.Q1). Sensitivity, and diagnostic accuracy were also significantly improved (p <0.01) to 0.96, and 0.99, respectively. Furthermore, kappa values were increased up to 0.82 - a relevant enhancement in the ability to precisely localize V/Q defects. Conclusion: In conclusion this protocol provides high-resolution tomographic scans as well as high-quality planar images within a short acquisition time. Due to the significant increase in lesion detection, sensitivity, diagnostic accuracy, and anatomical localization of defects, it is a substantial improvement in the diagnosis of pulmonary embolism that will put V/Q scintigraphy on a par with other tomographic methods.
Keywords: Single photon emission computed tomography; SPECT; pulmonary embolism; lung scintigraphy